Investigation of hand contact forces of female gymnasts performing a handspring vault - Penitente, G.; Sands, W. A.; McNeal, J.; Smith, S. L.; Kimmel, W. (International Journal of Sports Science and Engineering, 2010)
The purpose of this study was to characterize the normal (Fz) and anterior-posterior (Fx) hand contact forces of female gymnasts performing a handspring vault on the modern vault table. Twelve National Junior Olympic female gymnasts participated. The vault table was instrumented with two, two-dimensional calibrated portable force platforms, one for each hand. Each athlete performed two trials that were analyzed separately. Support phase duration ranged from 0.234, ±0.048 and 0.224, ±0.035 s for right and left hands, respectively. The force-time curves showed hand contact forces occurred in two phases, high values on impact followed by a longer and lower magnitudes that produced a forward-downward push. Average normal (vertical) peak force was 1.4, ±0.3 x body weight (BW). Hand contact differences in initial impact, duration, peak values and impulse showed marked differences between left and right hands. The results of this study indicate that hand contact force and time characteristics were variable and that symmetrical performance was not common and magnitudes could meet those necessary to injure the wrist and forearm. This first study of directly measured hand contact forces showed a lack of symmetry, and force-time curves that consisted of two distinct phases.